The apeman's secret - Dixon, Franklin W.; Morrill, Leslie H. (New York Simon & Schuster, 1980)
A "monster" who terrorizes Bayport and a girl who runs away to join a cult are the subjects of the Hardy boys' sleuthing.
Keywords: Mystery and detective stories